PENGARUH PROFITABILITAS, LEVERAGE, LIKUIDITAS, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2020) - Syachrul Yudi Habibie; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2022)
Earnings management is the manager's decision to choose certain accounting policies that are considered to be able to achieve the desired goals. The purpose of this research is to examine the effect of profitability, leverage, liquidity, and firm size on earnings management in manufacturing companies. The variables used in the test are profitability, leverage, liquidity, and firm size as independent variables, and earnings management as the dependent variable.Earnings management is measured using the modified Jones model, the modified Jones model focuses on total accruals (TAC) which is the total manipulation. This research data uses manufacturing companies during the 2016-2020 with total sample is 620 samples. Sampling based on purposive sampling method that follows certain criteria(s). Multiple regression analysis is the analysis is method used in research.The results of this study indicates that profitability has a positive effect on earnings management. This shows that companies that carry out earnings management are motivated because they want to get high profitability. Leverage has a significant positive effect on earnings management. This shows that companies with high leverage will carry out earnings management in the hope that they will still get funding sources from investors to pay off their obligations. Liquidity has a negative insignificant effect on earnings management. Meanwhile, firm size has a significant negative effect on earnings management. Companies with large company sizes will have good management and tend not to do earnings management, because they are required to provide accurate information.